Shift-Left Data Protection: The Architect’s Role in Embedding Agentic AI into DevSecOps - Bokka, Veera Venkata Ramana Murthy (IPHO-Journal of Advance Research in Science And Engineering, 2025)
This means data protection must commence during the design phase, rather than post-deployment, to solve the compliance debt crisis affecting today’s software development organizations. This article redefines the role of the enterprise architect as a governance orchestrator who embeds Agentic AI inside DevSecOps pipelines to transform compliance from a bottleneck in development into an automated assurance mechanism. In this regard, the architectural model proposes the use of three independent intelligence layers, including Guardian Agents that perform both dynamic and static application security tests with intelligent remediation recommendations; Policy Advisors that test the organizational policy and adapt to changes in regulations; and Feedback Agents that gather production telemetry to feed back the development-phase security controls. It also describes an implementation plan, which combines Azure DevOps and GitHub Actions to coordinate pipelines, Terraform to check infrastructure-as-code compliance, and Azure OpenAI to analyze semantic security findings. The empirical validation from the enterprise pilot demonstrates significant reductions in late-stage data protection issues, improved audit traceability, and reduced manual code review burdens. Consequently, the research establishes that architects need to design closed-loop feedback systems with codified guardrails, approval workflows, and automated rollback mechanisms in an attempt to balance autonomous operation with human oversight. This article shows that successful shift-left data protection is based on architectural decisions, which preside over agent placement, inter-agent communication protocols, and lifecycle management, plus organizational culture transformation to collaborative security ownership